About Bees, Mice and Purgatory. German Language Writing from the Experience of Nature - Wolting, Monika (Porównania, 2022)
The article deals with a new genre in German-language literature: nature writing. The genre has been enjoying success in the English literature market for some time, and only the first novels and volumes of this poetry appear in German-language literature that have arisen from the experience of nature; texts by Norbert Scheuer, Esther Kinsky, Marcel Bayer, Marion Poschmann, Laura Freundenthaler, Ulrike Draesner, Sabine Scho, Christian Lehnert, Silke Scheuermann and Gerhard Falkner should be mentioned here. The story “Der heißeste Sommer” ( 2020 ) by Laura Freudenthaler and the novel Winterbienen by Nobert Scheuer ( 2019 ) are presented as prime examples of this genre.